Use of ecosystem health indicators for assessing anthropogenic impacts on freshwaters in Argentina: a review - Rocha, Luciana (2020)
Indicators of ecosystem health are effective tools to assess freshwater ecosystem impairment. However, they are scarcely used as a monitoring tool by local environmental agencies in Argentina. Here, we review the literature to analyze the use of ecosystem health indicators in freshwaters from Argentina. We found 91 scientific articles relating to the use of ecological indices to assess the impact of different environmental stressors in aquatic environments published between 1996 and 2019. We generated Google Earth map where we deployed the sampling sites and type of indices reported by each article. As biological indices were the most used, we also surveyed bioindication experts to gather information on their application. We found that most studies were concentrated mainly in Pampas (34%), Dry Chaco (20%), Espinal (12%), and Patagonian Steppe (10%) ecoregions. Biological indices (mainly with invertebrates) were more used than geomorphological or physico-chemical indices. Indices resulted useful to evaluate the impact of stressors in 63% of cases, being land use the most studied stressor. However, sampling design varied greatly among studies, making their comparison difficult. The information compiled here could help to the design of monitoring protocols, the adoption of regional indices, and the creation of a national inventory of ecosystem health status, which are mandatory to propose well-grounded conservation and management policies for freshwaters in Argentina.